The complete chloroplast genome sequence of the medicinal plant Paris polyphylla (Melanthiaceae) - Zhao, Fei-Ya (Mitochondrial DNA B Resour, 2019)
Paris polyphylla is a medicinal plant commonly used in southwest of China. In this study, we sequenced the complete chloroplast (cp) genome sequence of P. polyphylla to investigate its phylogenetic relationship in the genus Paris. The chloroplast genome of P. polyphylla was 163,533 bp in length with 37.1% overall GC content, including a large single copy (LSC) region of 84,272 bp, a small single copy (SSC) region of 12,899 bp and a pair of inverted repeats (IRs) of 33,181 bp. The cp genome contained 114 genes, including 79 protein coding genes, 30 tRNA genes, and 4 rRNA genes. The phylogenetic analysis indicated P. polyphylla was closely related to P. marmorata.